A study of smart home: UUM student perspective - Muharor, Nurulhuda; Azman, Nur Ain Syazwani; Mohd Isa, Muhammad Azlan; Ismail, Noor Irwani; Samad, Siti Farah; Ahmad, Azhar (2015)
There are several issues related in housing development such as a continued rise in house prices became an issue for potential first time buyers and unsuccessful in the house industry that will contribute to homelessness for young generation and low-income wages. Therefore, a housing developer should identify the potential buyers’ criteria before designing the house to create uniqueness in housing industries.Innovation should be applied in developing innovative homes so that it will meet the affordable requirement for the potential buyers. Smart homes are a part of innovative home examples.A smart home is not just a home of the future, but rather an integrated way to wire a home to a network that controls all of function at once.The application of innovation in developing innovative homes will provide advantage to the developer’s business performance. This research is designed to investigate the relationship between innovative homes with business performance which reflects identifying the critical variable of innovative homes, investigating the requirements of potential buyers and examining the relationships of innovative homes with business performance. Besides using a survey to gather customer perceptions, this research will also employ key personnel perspectives into the analysis.It is expected that the findings could contribute towards greater understanding in view of innovative homes and business performance.This research is also expected to provide some innovative ideas for managerial applications in the housing industry.